Universities and teacher professional learning in the new policy context of teacher accreditation. Issue 5 (20th October 2021) - Nielsen, Wendy; Lipscombe, Kylie; Tindall-Ford, Sharon; Duchesne, Sue; Weatherby-Fell, Noelene; Sheridan, Lynn
ABSTRACT: All teachers in Australia must now achieve and maintain certification through mandatory accreditation processes that include specified professional learning hours. While key policies that outline teacher professional learning in Australia and New South Wales make no specific reference to a role for universities, this discussion paper proposes that the new teacher accreditation landscape provides opportunities for universities to work collaboratively with education systems to co-design and deliver contextually relevant teacher professional learning, support teachers-as-researchers and support schools to become learning communities. This collaboration would advance the policy agenda inherent in the accreditation processes by developing the intended culture of professional learning among teachers, education systems and universities that goes beyond mandated professional learning hours. We review the Australian policy context from a systems-thinking perspective and argue that university Schools and Faculties of Education (called SOE throughout this paper) work across multiple levels in education systems and are thus uniquely positioned to co-design and deliver relevant and contextually significant learning opportunities that foster teacher professional learning and school improvement.